2022
DOI: 10.1021/acsinfecdis.2c00123
|View full text |Cite
|
Sign up to set email alerts
|

An Updated View of the Trypanosoma cruzi Life Cycle: Intervention Points for an Effective Treatment

Abstract: Chagas disease (CD) is a parasitic, systemic, chronic, and often fatal illness caused by infection with the protozoan Trypanosoma cruzi . The World Health Organization classifies CD as the most prevalent of poverty-promoting neglected tropical diseases, the most important parasitic one, and the third most infectious disease in Latin America. Currently, CD is a global public health issue that affects 6–8 million people. However, the current approved treatments are limited to two nitrohete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 87 publications
0
41
0
5
Order By: Relevance
“…T. cruzi is typically transmitted through contaminated feces of an insect vector called triatomines or "kissing bugs," but oral transmission through ingestion of food contaminated with Triatomine feces, blood transfusions, and vertical transmission have also contributed. During the bloodmeal, male and female triatomines release feces containing flagellated parasites called trypomastigotes, which penetrate the body through the bite wound or through mucous membranes (Martıń-Escolano et al, 2022). As an obligate intracellular parasite, T. cruzi invades cells at the inoculum site (e.g.…”
Section: American Trypanosomiasis: Chagas Diseasementioning
confidence: 99%
“…T. cruzi is typically transmitted through contaminated feces of an insect vector called triatomines or "kissing bugs," but oral transmission through ingestion of food contaminated with Triatomine feces, blood transfusions, and vertical transmission have also contributed. During the bloodmeal, male and female triatomines release feces containing flagellated parasites called trypomastigotes, which penetrate the body through the bite wound or through mucous membranes (Martıń-Escolano et al, 2022). As an obligate intracellular parasite, T. cruzi invades cells at the inoculum site (e.g.…”
Section: American Trypanosomiasis: Chagas Diseasementioning
confidence: 99%
“…In endemic areas, the disease is transmitted by blood-sucking insects of the subfamily Triatominae, which can infect a mammalian host [ 5 ]. The T. cruzi parasite is an intracellular protozoan that can undergo a complex life cycle between the insect vector and a mammalian host [ 5 , 6 , 7 ]. The parasite adopts four main forms during its life cycle: two in the insect vector, which are epimastigotes (replicative form) and metacyclic trypomastigotes (non-replicative and infectious form) [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The T. cruzi parasite is an intracellular protozoan that can undergo a complex life cycle between the insect vector and a mammalian host [ 5 , 6 , 7 ]. The parasite adopts four main forms during its life cycle: two in the insect vector, which are epimastigotes (replicative form) and metacyclic trypomastigotes (non-replicative and infectious form) [ 5 , 6 , 7 ]. The mammalian host also adopts two forms, amastigote (replicative intracellular form) and blood trypomastigote (non-replicative form) [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 New drugs should also achieve total clearance of parasites in patients to prevent relapse after treatment. 11 In recent years, combination therapies that utilize multiple drugs with different mechanisms of action have been found to be effective in preclinical testing. 12,13 While combinations have been tested in clinical trials, their efficacy compared to individual drug components alone have yet to be identified.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hence, ideal TPPs focus on new regimens that have a shorter treatment course, are safe and more efficacious than current drugs, exhibit good oral bioavailability, and are active against both chronic and acute phases . New drugs should also achieve total clearance of parasites in patients to prevent relapse after treatment . In recent years, combination therapies that utilize multiple drugs with different mechanisms of action have been found to be effective in preclinical testing. , While combinations have been tested in clinical trials, their efficacy compared to individual drug components alone have yet to be identified …”
Section: Introductionmentioning
confidence: 99%